Reductive Thermal ALD of Pd and Pd2Ge From a Novel Recyclable Palladium Chloride Adduct - Anton Vihervaara; Timo Hatanpää; Mikko‐Ilmari Selänne; Kenichiro Mizohata; Mikko Ritala (Advanced Materials Interfaces)
Abstract In this work, a new ALD process for palladium metal thin films using dichlorobis(triethylphosphine)palladium(II) (PdCl2(PEt3)2) and 1,4‐bis(trimethylsilyl)‐1,4‐dihydropyrazine ((Me3Si)2DHP) as reactants, is developed. The metal precursor is chosen based on the known reactivity of metal halides with the DHP‐type reducing agents. Metallic Pd films are deposited at temperatures of 140–180 °C with a growth rate of 0.3–0.4 Å cycle−1. Furthermore using 1,4‐bis(trimethylgermyl)‐1,4‐dihydropyrazine ((Me3Ge)2DHP) as the co‐reactant yielded Pd2Ge thin films. Finally, full recyclability of the PdCl2(PEt3)2 is observed: unused molecules condensed in the exhaust tube can be collected by dissolving them into acetone, purified by recrystallization, and reused.